6m-8+2=9m-1

Simple and best practice solution for 6m-8+2=9m-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m-8+2=9m-1 equation:


Simplifying
6m + -8 + 2 = 9m + -1

Reorder the terms:
-8 + 2 + 6m = 9m + -1

Combine like terms: -8 + 2 = -6
-6 + 6m = 9m + -1

Reorder the terms:
-6 + 6m = -1 + 9m

Solving
-6 + 6m = -1 + 9m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-9m' to each side of the equation.
-6 + 6m + -9m = -1 + 9m + -9m

Combine like terms: 6m + -9m = -3m
-6 + -3m = -1 + 9m + -9m

Combine like terms: 9m + -9m = 0
-6 + -3m = -1 + 0
-6 + -3m = -1

Add '6' to each side of the equation.
-6 + 6 + -3m = -1 + 6

Combine like terms: -6 + 6 = 0
0 + -3m = -1 + 6
-3m = -1 + 6

Combine like terms: -1 + 6 = 5
-3m = 5

Divide each side by '-3'.
m = -1.666666667

Simplifying
m = -1.666666667

See similar equations:

| 2.5-x=3.5 | | y^2=x+2 | | 8w*3=152 | | -6=.75(y+2) | | 0.6k+5=7 | | -1=9-.666x | | 52.5(3-x)=315 | | (8)+(-1)= | | 175(n-2)=700 | | ab+c= | | -1=9-.33x | | 9x-15=30+4x | | 1x-21=-8 | | 12x^2-21x-45=0 | | -8x+80=-4x+44 | | 8s-20=32+6s | | 3b+b=16 | | 9+xy= | | 4*4+10y=40 | | 4z+3=23 | | 5p-6+p=14-2p | | 6x-31=4x-19 | | 56=8+3(y+4) | | 2x-7=5+x | | 11(a+b)= | | v=lwh*w | | -6y+10+4y=32 | | 5x+7=8x-(x+1) | | -4n=2 | | 5x+2(11-4x)=84+x | | 18a+4=-8 | | 6x^2-7xy-5y^2=0 |

Equations solver categories